Macromolecular chemistry-- 8 : Plenary and main lectures presented at the International Symposium on Macromolecules held in Helsinki, Finland, 2-7 July, 1972 - Saarela, Kerttu (Butterworths, 1973)
Macromolecular Chemistry focuses on the molecular configuration of polymers, charge-transfer complexes, polymerization reactions, molecular weight fractionation, and polymer systems. The selection first offers information on molecular configuration in bulk polymers and control of monomer reactivity in copolymerization. Discussions focus on thermodynamic behavior of concentrated polymer solutions; direct measurement of molecular dimensions; and modification of monomer reactivity in radical copolymerization. The book also ponders on non-equimolar compositions from comonomer charge-transfer.